Understanding of the socio-economic impact of PAMANA initiatives in conflict-affected areas in the Philippines - Catada Gapasin Merivic; Atillo Abiera Guilbert Nicanor (Ho Chi Minh City Open University Journal of Science - Social Sciences)
This study examines the socio-economic impact of PAMANA development initiatives in conflict-affected areas of Negros Oriental, Philippines, employing a descriptive survey methodology. It focuses on profiling beneficiary respondents, identifying implementation challenges, and evaluating the projects’ social and economic effects. Despite PAMANA’s implementation since 2016, there has been a lack of comprehensive monitoring and evaluation, which has prompted this research. Coordination meetings with farmer associations and LGUs facilitated data collection using descriptive survey questionnaires from 13 geographically dispersed associations, primarily comprising farmers and active PAMANA participants. Analysis of responses from 272 beneficiaries reveals the challenges faced by beneficiaries of the PAMANA program, including inadequate project monitoring, leadership deficiencies, and communication gaps. The Covid-19 pandemic has further exacerbated these challenges, leading to economic uncertainty among participants. While some respondents reported successful program implementation, a significant portion expressed dissatisfaction with its impact on health services, education, and financial improvement. Addressing these concerns requires a comprehensive approach, including enhancing communication strategies, fostering leadership development, and identifying and rectifying program shortcomings. Overall, the findings underscore the need for targeted interventions to improve the PAMANA program’s effectiveness in supporting its beneficiaries’ economic and social well-being. Policymakers can use this evidence to formulate policies and strategies grounded in data-driven insights, enhancing the likelihood of achieving desired socio-economic outcomes. Finally, the result provides new empirical evidence and analysis that enriches scholarly understanding of the intersection between development interventions and peacebuilding efforts.